2020
DOI: 10.1097/pgp.0000000000000683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Apoptosis, Proliferation, and Adhesion Molecule Expression in Trophoblastic Tissue of Women With Recurrent Spontaneous Abortion and Infected With Toxoplasma gondii

Abstract: Recurrent spontaneous abortion is an obstetric complication with undefined causes. Apoptosis, proliferation, and adhesion are considered important factors in the pathogenesis of abortion. This work aimed to determine Bax and Bcl-2 as a proapoptotic and antiapoptotic protein, Ki67 and P27kip as proliferative and antiproliferative proteins, and E-cadherin and CD44 as adhesion molecules in the trophoblastic tissues in cases with recurrent miscarriage. Immunohistochemistry and quantitative polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Schistosoma japonicum can promote cell apoptosis by increasing the expression of Fas and FasL in CD 4+ and CD 8+ T cells ( Lundy et al, 2001 ). When Toxoplasma gondii infected the embryo trophoblast, the expression of Bax and P27 proteins in host cells increased, and the apoptosis rate of host cells increased ( Elsalam et al, 2021 ). After chickens were infected with E. tenella , the concentration of calcium ions and reactive oxygen species in the cecal mucosa and intestinal gland epithelial cells of chickens increased, thereby promoting the apoptosis of cecal cells ( Zhang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schistosoma japonicum can promote cell apoptosis by increasing the expression of Fas and FasL in CD 4+ and CD 8+ T cells ( Lundy et al, 2001 ). When Toxoplasma gondii infected the embryo trophoblast, the expression of Bax and P27 proteins in host cells increased, and the apoptosis rate of host cells increased ( Elsalam et al, 2021 ). After chickens were infected with E. tenella , the concentration of calcium ions and reactive oxygen species in the cecal mucosa and intestinal gland epithelial cells of chickens increased, thereby promoting the apoptosis of cecal cells ( Zhang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…BCL-2, an anti-apoptotic protein, plays a key role in regulating endometrial cell turnover (35). A recent study reported that BCL-2 expression was reduced in trophoblastic tissues of patients with RSAs (36). Similarly, a reduction in BCL-2 expression was discovered in the villi of patients with RSAs, suggesting that low BCL-2 expression may be associated with RSA.…”
Section: Discussionmentioning
confidence: 99%
“…After each incubation, the slide was dipped in a buffer for 5 minutes. EnVision™ FLEX Hematoxylin did the counterstaining, then dehydration by deionized water, and finally the slides were mounted with a coverslip using DPX (BDH Clinical, Merck, USA) (10,11) . The use of kidney tissue provided positive control.…”
Section: Immunohistochemistrymentioning
confidence: 99%